Effects of strains on growth performances of triploid bighead catfish, Clarias macrocephalus Günther, 1864 - Chatchaiphan, Satid; Srisapoome, Prapansak; Na-Nakorn, Uthairat (Agriculture and Natural Resources, 2016)
Despite its importance, limited empirical information is available on the effects of parental strains on the performance of triploid aquatic animals, especially of tropical species. The present study was conducted to evaluate the impacts of strains on the growth performance of the triploid bighead catfish (Clarias macrocephalus Günther, 1864) which was produced using cold shock (7 oC, 25 min shock duration), applied to newly fertilized eggs obtained from all possible crosses between two catfish strains. The fingerlings of each group were reared until they were age 240 d. At age 60 d, the triploid fish had a lower specific growth rate (SGR), absolute growth rate (AGR), body length and body weight than the diploid counterparts. However, at harvest (age 240 d) body length and body weight were not different between the two groups while SGR of the cold shock group was higher than the diploid during age 121-240 d. The results revealed that parental strains did not show significant direct effects on the growth performance of triploids, but the interaction between paternal strain x shock was significant for the following traits: body length at age 90 d, body weight at age 90 d and 120 d, AGR for age 61-90 d, and SGR for age 61-90 d and 91-120 d. The interaction between paternal x maternal strain x shock was significant for body length, body weight at age 180 d and AGR for age 121-180 d. These results suggested that the growth performance of triploid C. macrocephalus cannot be enhanced by improving the parental strains; rather, improvement may be accomplished by selecting the parental strains based on triploid performance.